A Preconditioning Strategy to Augment Retention and Engraftment Rate of Donor Cells During Hepatocyte Transplantation. Issue 4 (22nd September 2020) - Hsu, Yu-Chen; Yu, I-Shing; Tsai, Yu-Fei; Wu, Yao-Ming; Chen, You-Tzung; Sheu, Jin-Chuan; Lin, Shu-Wha
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Hepatocyte transplantation has been extensively investigated as an alternative to orthotopic liver transplantation. However, its application in routine clinical practice has been restricted because of low initial engraftment and subsequent repopulation. Methods: Using mice as a model, we have developed a minimally invasive and nontoxic preconditioning strategy based on preadministration of antibodies against hepsin to increase donor hepatocyte retention and engraftment rate. Results: Liver sinusoid diameters decreased significantly with antihepsin pretreatment, and graft cell numbers increased nearly 2-fold in the recipients' liver parenchyma for 20 days after hepatocyte transplantation. Postoperative complications such as hepatic ischemia injury or apparent immune cell accumulation were not observed in recipients. In a hemophilia B mouse model, antihepsin preconditioning enhanced the expression and clotting activity of coagulation factor IX (FIX) to nearly 2-fold that of immunoglobulin G–treated controls and maintained higher plasma FIX clotting activity relative to the prophylactic range for 50 days after hepatocyte transplantation. Antihepsin pretreatment combined with adeno-associated virus−transduced donor hepatocytes expressing human FIX-Triple, a hyperfunctional FIX variant, resulted in plasma FIX levels similar to those associated with mild hemophilia, which protected hemophilia B mice from major bleeding episodes for 50 days after transplantation. Furthermore, antihepsin pretreatment and repeated transplantation resulted in extending the therapeutic period by 30 days relative to the immunoglobulin G control. Conclusions: Thus, this antihepsin strategy improved the therapeutic effect of hepatocyte transplantation in mice with tremendous safety and minimal invasion. Taken together, we suggest that preconditioning with antihepsin may have clinical applications for liver cell therapy.